Ecotourism Development Strategy Of Mount Baung Nature Tourism Park, Pasuruan Regency, East Java Province - Kurniawan, Nur Patria; Bugiono, Bugiono; Komara, Liris Lis (Fakultas Kehutanan Universitas Mulawarman, 2026)
Developing ecotourism as a transformative tourism model based on nature conservation, environmental education, and improving the welfare of local communities is a key agenda in Indonesian conservation areas. This research aims to formulate an optimal and sustainable ecotourism development strategy in the Mount Baung Nature Tourism Park, Pasuruan Regency, East Java. The method used was descriptive with a mixed approach (qualitative-quantitative), including direct observation, interview surveys with managers and 30 tourists, and document review. Strategy formulation was conducted using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and the IFAS and EFAS matrices to evaluate the area's internal and external factors.The research identified significant potential for the Mount Baung National Park, including: biological potential (unique bamboo forests, shade-providing flora, and fauna) and non-biological potential (100-meter-high Coban Baung Waterfall and steep). A site carrying capacity analysis confirmed the area's ideal location for controlled ecotourism. Based on a SWOT analysis, the Mount Baung Nature Tourism Park is located in Quadrant I (Strengths-Opportunities), indicating excellent conditions and the need for an aggressive growth strategy (Growth-Oriented Strategy). The main strategies formulated include protecting and securing the area, restoring the ecosystem, developing educational tourism potential (including Mini Hydro power), enhancing management professionalism, and strengthening partnerships.